2023
DOI: 10.3390/medicina59020305
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Biportal Endoscopic Laminectomy for Treating Cervical Stenosis: A Technical Note and Preliminary Results

Abstract: Objective: The objective of this study was to introduce a surgical technique for the percutaneous decompression of cervical stenosis (CS) using a unilateral biportal endoscopic approach and characterize its early clinical and radiographic results. Materials and Methods: Nineteen consecutive patients with CS who needed surgical intervention were recruited. All enrolled patients underwent unilateral biportal endoscopic laminectomy (UBEL). All patients were followed postoperatively for >1 year. The preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some studies have demonstrated that UBE laminectomy may be considered an excellent surgical alternative to treat cervical stenosis without the development of iatrogenic kyphosis [ 93 ]. It represents an effective method with excellent neurological and radiological outcomes with less soft tissue invasion, which translates into dramatically less postoperative axial pain and maintains postoperative cervical lordosis [ 93 ].…”
Section: Cervical Spine Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that UBE laminectomy may be considered an excellent surgical alternative to treat cervical stenosis without the development of iatrogenic kyphosis [ 93 ]. It represents an effective method with excellent neurological and radiological outcomes with less soft tissue invasion, which translates into dramatically less postoperative axial pain and maintains postoperative cervical lordosis [ 93 ].…”
Section: Cervical Spine Endoscopymentioning
confidence: 99%
“…Some studies have demonstrated that UBE laminectomy may be considered an excellent surgical alternative to treat cervical stenosis without the development of iatrogenic kyphosis [ 93 ]. It represents an effective method with excellent neurological and radiological outcomes with less soft tissue invasion, which translates into dramatically less postoperative axial pain and maintains postoperative cervical lordosis [ 93 ]. Wang et al concluded in their study that UBE and Percutaneous posterior endoscopic discectomy were both safe and effective in the treatment of cervical spondylotic radiculopathy and were characterized by minimal trauma, no adverse impact on cervical stability, and few complications [ 94 ].…”
Section: Cervical Spine Endoscopymentioning
confidence: 99%
“…It represents an effective method with excellent neurological and radiological outcomes with less soft tissue invasion, which translates into dramatically less postoperative axial pain and maintained postoperative cervical lordosis (93). Wang et al concluded in their study that UBE and PE (percutaneous posterior endoscopic discectomy) were both safe and effective in the treatment of cervical spondylotic radiculopathy and were characterized by minimal trauma, no adverse impact on cervical stability and few complications (94). It is safe to say that cervical endoscopic surgeries have evolved and are no longer limited to dealing with just single level disc disease.…”
Section: Cervical Spine Endoscopymentioning
confidence: 99%
“…A well-trained surgeon then uses specialized instruments to remove the bony structure or herniated disc without affecting the surrounding healthy tissues. Several reports on the technical notes and clinical outcomes of C-BESS have recently been published [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%